A matemática aplicada aos quadricópteros: uma proposta de ensino e pesquisa - Silva Filho, Télico José de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
This paper aims to discuss the mathematics used in the quadcopter as a teaching and research tool in high school and how the knowledge produced in academic research in this area can be a motivating element for students and teachers. With this, the work aims to arouse interest in knowing applications of mathematics in technology. It seeks to base on the teaching proposals of STEM, for science, technology, engineering and mathematics, making use of tools such as Didactic Transposition of Knowledge and Translational Research. Following these methodological assumptions, a study was made of the mathematical and physical tools employed in constructing a quadricopter model using basically matrices, differential equations and Newton’s laws. Then, the vehicle was modeled, arriving at a system of differential equations and finally, the quadricopter control is discussed. Based on the rules of Didactic Transposition of Knowledge, STEM teaching and already developed practices, it is fully possible to transpose this knowledge to High School.
Keywords: Modelagem; Transposição didática; Ensino de STEM; Quadricóptero; Modeling; Didactic Transposition; STEM teaching; Quadcopter; CIENCIAS EXATAS E DA TERRA::MATEMATICA